Spectrophotometric Determination of Dimethindene in Pharmecutical Preparations and Water Samples - Nief Ahmed (College of Education for Pure Sciences, 1999)
ABSTRACT A simple, accurate, rapid and sensitive visible spectrophotometric method has been developed for the determination of dimethindene in pure and pharmaceutical preparations. The method is based on the reaction of dimethindene with potassium permanganate in alkaline solution to form a bluish green coloured chromogen with an absorption maximum at 610 nm. Beer's Law was obyed in the range of 0.2-2.8 µg/ml with molar absorbitivity of 4×103 L.mol.-1.cm-1. The optimum conditions for all colour development are described and the propsed method has been successfully applied for the determination of dimethindene in pharmaceutical preparations and water samples. The common excipients and additives did not interfere in the proposed method.